Exploring the coherence between the EFL curriculum policy and its implementation in the higher education setting - Adriadi Novawan; Siti Aisyiyah; Fitri Wijayanti; Asep Samsudin (Politeknik Negeri Jember, 2018)
This paper reports the results of a case study which explored the reality of ELT curriculum implementation in the higher education setting in Indonesia in light of the notion of coherence. The study was underpinned by naturalistic inquiry and was intended to know the extent to which the national curriculum policy was implemented in the individual higher education institution through the institutional curriculum policy and in turn was implemented through classroom instructions and experienced by the students. The data were collected by using documentation, interviews, and observations, and analyzed by using the Immersion/Crystallization method. The major finding was that the implementation of the ELT curriculum in the institutional level might not represent the vision of national curriculum policy. The institutional policy announced the application of curriculum on the basis on IQF (Indonesian Qualification Framework), nevertheless, divergent interpretation toward the national policy had led to bias implementation in the level of the department. While most subjects within the overarching (department) curriculum were directed to adopt a strong product-oriented model, the English subjects represented a different reality.Â Â Keywords: higher education, EFL curriculum, coherence, policy, and practice